Ultrasound-enhanced thrombolysis with tPA-loaded echogenic liposomes - Shaw, George J.; Meunier, Jason M.; Huang, Shao-Ling; Lindsell, Christopher J.; McPherson, David D.; Holland, Christy K. (Thrombosis research, 2009)
Currently, the only FDA-approved therapy for acute ischemic stroke is the administration of recombinant tissue plasminogen activator (tPA). Echogenic liposomes (ELIP), phospholipid vesicles filled with gas and fluid, can be manufactured to incorporate tPA. Also, transcranial ultrasound-enhanced thrombolysis can increase the recanalization rate in stroke patients. However, there is little data on lytic efficacy of combining ultrasound, echogenic liposomes, and tPA treatment. In this study, we measure the effects of pulsed 120-kHz ultrasound on the lytic efficacy of tPA and tPA-incorporating ELIP (t-ELIP) in an in-vitro human clot model. It is hypothesized that t-ELIP exhibits similar lytic efficacy to that of rt-PA. Blood was drawn from 22 subjects after IRB approval. Clots were made in 20-µL pipettes, and placed in a water tank for microscopic visualization during ultrasound and drug treatment. Clots were exposed to combinations of [tPA] = 3.15 µg/ml, [t-ELIP] = 3.15 µg/ml, and 120-kHz ultrasound for 30 minutes at 37 °C in human plasma. At least 12 clots were used for each treatment. Clot lysis over time was imaged and clot diameter was measured over time, using previously developed imaging analysis algorithms. The fractional clot loss (FCL), which is the decrease in mean clot width at the end of lytic treatment, was used as a measure of lytic efficacy for the various treatment regimens. The fractional clot loss FCL was 31% (95% CI: 26-37%) and 71% (56-86%) for clots exposed to tPA alone or tPA with 120 kHz ultrasound. Similarly, FCL was 48% (31-64%) and 89% (76-100%) for clots exposed to t-ELIP without or with ultrasound. The lytic efficacy of tPA containing echogenic liposomes is comparable to that of tPA alone. The addition of 120 kHz ultrasound significantly enhanced lytic treatment efficacy for both tPA and t-ELIP. Liposomes loaded with tPA may be a useful adjunct in lytic treatment with tPA.